Conserved Function of Fibrillin5 in the Plastoquinone-9 Biosynthetic Pathway in Arabidopsis and Rice - Kim, Eun-Ha; Lee, Dae-Woo; Lee, Kyeong-Ryeol; Jung, Su-Jin; Jeon, Jong-Seong; Kim, Hyun Uk (Frontiers in Plant Science, 2017)
Plastoquinone-9 (PQ-9) is essential for plant growth and development. Recently, we found that fibrillin5 (FBN5), a plastid lipid binding protein, is an essential structural component of the PQ-9 biosynthetic pathway in Arabidopsis. To investigate the functional conservation of FBN5 in monocots and eudicots, we identified OsFBN5, the Arabidopsis FBN5 (AtFBN5) ortholog in rice (Oryza sativa). Homozygous Osfbn5-1 and Osfbn5-2 Tos17 insertion null mutants were smaller than wild type (WT) plants when grown on Murashige and Skoog (MS) medium and died quickly when transplanted to soil in a greenhouse. They accumulated significantly less PQ-9 than WT plants, whereas chlorophyll and carotenoid contents were only mildly affected. The reduced PQ-9 content of the mutants was consistent with their lower maximum photosynthetic efficiency, especially under high light. Overexpression of OsFBN5 complemented the seedling lethal phenotype of the Arabidopsis fbn5-1 mutant and restored PQ-9 and PC-8 to levels comparable to those in WT Arabidopsis plants. Protein interaction experiments in yeast and mesophyll cells confirmed that OsFBN5 interacts with the rice solanesyl diphosphate synthase OsSPS2 and also with Arabidopsis AtSPS1 and AtSPS2. Our data thus indicate that OsFBN5 is the functional equivalent of AtFBN5 and also suggest that the SPSs-FBN5 complex for synthesis of the solanesyl diphosphate tail in PQ-9 is well conserved in Arabidopsis and rice.